Second-Semester Students’ Challenges towards Vocabulary Mastery in English Language Learning - Telaumbanua, Yasminar Amaerita; Mendrofa, Denista Riska Cahyani; Hura, Mince Resti Natalia; Waruwu, Asirida; Tafona'o, Priskila Destalenta (English Teaching and Linguistics Journal (ETLiJ), 2024)
This study aims to identify the challenges and inhibiting factors that affect vocabulary acquisition in English language learning. The research was conducted using a qualitative method, specifically through structured interviews. Descriptive research was also employed to process the data. The participants were 32 second-semester students from the English Education Study Program at Universitas Nias. Six questions were prepared for the participants, with responses based on their personal experiences. The results revealed that many participants cited laziness as a significant factor hindering their vocabulary improvement, largely due to their infrequent use of English in daily life. Other factors included low motivation and interest, difficulties with word meaning and grammar, and challenges with pronunciation. These factors were categorized into psychological factors—such as low motivation, interest, and laziness in memorizing words—and linguistic factors, which included difficulties with word meaning, grammar, and pronunciation. Additional reasons identified were a lack of confidence in speaking English with others, frequent forgetting of vocabulary, difficulty understanding context, learning dependent on mood, and limited study time. These were further classified into psychological factors, such as lack of confidence and study laziness, and cognitive factors, like difficulty remembering vocabulary.